Identificación de los principales daños causados por botritys en el cultivo de mora de Castilla (Rubus glaucus Benth), en la parroquia de Maldonado, cantón Tulcán, provincia del Carchi - García Puedmag, Carmen Liliana (2019)
SUMMARY The present research work was carried out in the parish of Maldonado, Tulcán Ridge, province of Carchi, located at coordinates 0 ° 15'5 north latitude, 78 ° 35'0 west longitude and at an altitude of 4000 msnml, conditions The climatological indicators of the area show an annual average of 89%, relative humidity 83%, wind 11km /h and a temperature of 20 ° C, sub-tropical climate sector. The cultivation of blackberry in the area is of great importance because it is one of the oldest cultivating in a traditional way without any type of tutorado, they do not carry out pruning of formation, maintenance and fructification, the phytosanitary controls are carried out at the moment they are presented damage caused by pests in an area of 1 hectare for more than 10 years. The damages caused by botrytis in the cultivation of blackberry of castile present gray mold usually in the fruits, also affects flowers and stems in smaller degree, in the epoch where a greater attack of botrytis is registered is in the fructification and in the vegetative stage is recorded the least attack, the factors that intervene in the proliferation of the fungus in the cultivation of blackberry are the presence of excessive rainfall and climatic conditions, control methods to prevent the attack of this pest is chemical control, taking in view of the economic importance of this crop, it would be pertinent to deepen the studies of an integrated management of pests and diseases (MIPE), considering the damage threshold and conducting training and field days to fully identify botrytis and the control methods that are you could use. Keywords: botrytis, diseases, control, management, tutorado, proliferation